The Cost-Effectiveness of Tislelizumab Plus Chemotherapy for Locally Advanced or Metastatic Nonsquamous Non-Small Cell Lung Cancer - Luo, Xia; Zhou, Zhen; Zeng, Xiaohui; Liu, Qiao (Frontiers in Pharmacology, 2022)
Objective To investigate the cost-effectiveness of adding Chinese-developed anti-PD-1 antibody tislelizumab to first-line pemetrexed-platinum chemotherapy in (1) a study population of patients with locally advanced or metastatic nonsquamous non-small cell lung cancer (nsqNSCLC) and without driver gene mutations; and (2) its subgroups from the perspective of Chinese healthcare system. Material and Methods Separate Markov models were constructed for the entire study population and its subgroups; 10,000 patients with locally advanced or metastatic nsqNSCLC and without driver gene mutations were simulated in the first-line tislelizumab plus pemetrexed-platinum (TPP) arm and first-line pemetrexed-platinum (PP) arm, respectively. Transition probabilities were extracted from the RATIONALE 304 trial. Health state utilities and costs were obtained from published literature, publicly national databases, and local general hospitals. The main outputs were incremental cost-effectiveness ratios (ICERs). The ICERs were compared to a willingness-to-pay threshold of $35,663 per quality-adjusted life-years (QALYs) to determine the cost-effective treatment. Sensitivity analyses were employed to assess the uncertainty in the model. Results For the entire patient population, first-line TPP versus PP use increased the effectiveness by 0.99 QALYs and healthcare costs by $28,749, resulting in an ICER of $28,749/QALY that was lower than the prespecified WTP threshold. For patient subgroups, first-line TPP conferred the greatest survival benefit in patients with PD-L1 expression ≥50% , followed by patients with liver metastasis and those who are current and former smokers. Overall, the ICERs for the first-line TPP versus PP ranged from $27,018/QALYs to $ 33,074/QALYs, which were consistently below the WTP threshold. Conclusion For Chinese patients with locally advanced or metastatic nsqNSCLC, adding Chinese-developed anti-PD-1 antibody tislelizumab to the first-line pemetrexed-platinum chemotherapy was cost-effective regardless of their baseline characteristics.